Phenotypic screening in zebrafish larvae identifies promising cyanobacterial strains and pheophorbide a as insulin mimetics - Tiago Ribeiro; Mariana Reis; Vitor Vasconcelos; Ralph Urbatzka (Scientific Reports)
Abstract Diabetes is a pandemic disease that causes the loss of control of glucose regulation in the organism, in consequence of dysfunction of insulin production or functionality. In this work, the antidiabetic bioactivity of 182 fractions from 19 cyanobacteria strains derived from the LEGE Culture Collection were analysed using the 2-NBDG assay in zebrafish larvae. From this initial screening, two fractions (57 (06104_D) and 107 (03283_B)) were identified as promising insulin mimetics. These were further characterized by measuring glucose levels in whole larvae, the expression of glucose transporters (GLUT 1–3) using western blot, and the mRNA expression levels of the glut2, pepck, and insa genes using real-time qPCR. Both fractions showed a decrease in free glucose levels. Furthermore, exposure to fraction 06104_D decreased GLUT1 and increased insa mRNA levels. The chemical composition of these fractions was determined using LC-HRESIMS/MS and compared to inactive fractions of the same polarity in order to identify the unique bioactive molecules. The molecular networks constructed using the GNPS platform revealed that fraction 06104_D contained mass clusters primarily composed of chlorins, lipids, and terpenoids, while fraction 03283_B contained xanthophylls, peptides, and terpenoids. To correlate the observed activity with the chemical composition of fraction 06104_D, pheophorbide a was chosen as a representative of chlorophyll derivatives. Exposure to zebrafish larvae at 10 and 20 µM confirmed the increased glucose uptake on the 2-NBDG assay. These findings highlight the bioactivity of chlorophyll derivatives as insulin mimetic compounds, as well as cyanobacteria as a source of potential therapeutic diabetes applications.